Measuring and Managing Go-Jek Driver Delivery Quality with COBIT Framework - Bie, Kalistowen; Suliana, I Made; Azmi, Muhammad; Sabrila, Trifebi Shina; Latif, Abdul; Lindawati, Ratna (LPPM Universitas Sari Mulia, 2024)
This research explores methods and strategies to more effectively measure and manage the delivery quality performed by Gojek drivers. In the digital era, app-based transportation services like Gojek have become an integral part of society. Ensuring high delivery quality requires a deep understanding of influencing factors such as timeliness, condition of goods, and customer satisfaction. By leveraging technology and data analysis, Gojek can identify areas needing improvement and implement appropriate solutions. This study uses the COBIT 5 framework to assess and enhance delivery quality. The findings indicate that the IT governance maturity level of Gojek in the EDM 02 and DSS 03 domains is at level 3 (Established). However, there is a gap that needs to be addressed to reach the desired level of 5 (Optimizing). Recommendations are provided to bridge this gap by implementing consistent standard processes across the company.